2014
DOI: 10.1590/0074-0276140096
|View full text |Cite
|
Sign up to set email alerts
|

JVG9, a benzimidazole derivative, alters the surface and cytoskeleton of Trypanosoma cruzi bloodstream trypomastigotes

Abstract: Trypanosoma cruzi has a particular cytoskeleton that consists of a subpellicular network of microtubules and actin microfilaments. Therefore, it is an excellent target for the development of new anti-parasitic drugs. Benzimidazole 2-carbamates, a class of well-known broad-spectrum anthelmintics, have been shown to inhibit the in vitro growth of many protozoa. Therefore, to find efficient anti-trypanosomal (trypanocidal) drugs, our group has designed and synthesised several benzimidazole derivatives. One, named… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…In this context, benzimidazole derivatives synthetized by our group have shown biological activity against several parasites [ 31 , 32 , 33 , 34 , 35 ], and some of them have shown inactivation of Trypanosoma cruzi TIM (TcTIM) [ 36 , 37 , 38 ]. In the present work, we searched TbTIM inactivators from our in house library of benzimidazole derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, benzimidazole derivatives synthetized by our group have shown biological activity against several parasites [ 31 , 32 , 33 , 34 , 35 ], and some of them have shown inactivation of Trypanosoma cruzi TIM (TcTIM) [ 36 , 37 , 38 ]. In the present work, we searched TbTIM inactivators from our in house library of benzimidazole derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo short-term evaluation of the trypanocidal activity of the FDA-approved drugs. Six groups of six CD1 female mice were infected with blood trypomastigotes of Ninoa and INC-5 strains following the methodology previously described in Romanha et al [ 111 ] and in Díaz-Chiguer et al [ 112 ]. At day 13 post-infection, when the infected mice reached an average of 5 × 10 6 parasites/mL, a single dose of the FDA-approved drugs at 100 mg/kg body weight was orally administered.…”
Section: Methodsmentioning
confidence: 99%
“…Alterations in the plasma membrane are usually related on T. cruzi under treatment with different drugs due to the osmotic stress unleashed or the attempt of the parasite to promote the shedding of the compound. 37 , 38 Interestingly, several studies using human and murine cell models demonstrated that HIV-IPs extensively affect the mitochondrion and the endoplasmic reticulum. Misbalance in these organelles are directly associated with lipid disturbances induced by HIV-PIs in HIV-positive patients.…”
mentioning
confidence: 99%